Projeto e implementação de automação em uma máquina de casquinhas de sorvete - CALDEIRA, Higor Marques (2021)
It is proposed to apply automation practices to make a cone machine built locally commercially viable. The machine used was altered applying automation principles seeking to make it easier to use, cheaper to build maintain and raise its general efficiency. Functionality of the machine were analyzed, like precision in the cone production, hard and slow maintenance processes, absence of an automatic mode, and so on. After identifying and analyzing the problems the cone machine has, a solution was designed based on Ladder coding language to automate the cone machine use. The machine’s schematic were rebuilt, reusing positive points of the machine and ditching out negative ones. At the end of testing all of the new implementation, it is concluded that the cone machine became a tool with a higher competitive value for local entrepreneurs, holding enhancements in its costs, performance, maintenance, quality of the cones and is easy to run on a small local business of the industry.